EFFECT OF HEALTHY HEART GYMNASTICS SERIES-I IN INCREASING CARDIORESPIRATORY ENDURANCE IN THE ELDERLY - Dewi, Ni Ketut Cintya; Suadnyana, Ida Ayu Astiti; Manuaba, I.A. Ratih Wulansari; Tunas, I Ketut (Jurnal Kesehatan Saintika Meditory, 2025)
Aging is an inevitable natural process, and one of its impacts is the decline in the cardiorespiratory system. Preventive efforts can be made by increasing physical activity as early as possible during the pre-elderly phase (45-59 years). This study aimed to determine the effect of Healthy Heart Exercise Series-I on cardiorespiratory endurance in the elderly in Banjar Dakdakan, Peguyangan Village, North Denpasar District. This pre-experimental study used a pre-test and post-test one-group design conducted from April to May 2024, involving 15 research participants who met the inclusion and exclusion criteria. The sampling technique used was purposive sampling. The instrument used to measure cardiorespiratory endurance was the six-minute walking test, which was then converted into VO2Max values. Data were analyzed using the Wilcoxon signed-rank test to determine the effect of Healthy Heart Exercise Series-I on cardiorespiratory endurance in the elderly. The analysis results showed a p-value of 0.001 (p<0.05), indicating a significant difference in the improvement of VO2Max before and after the intervention in the elderly group who received the treatment. It was concluded that Healthy Heart Exercise Series-I positively affects cardiorespiratory endurance in the elderly in Banjar Dakdakan, Peguyangan Village, North Denpasar District.